Effect of adhesive fillet geometry on bond strength between microelectronic components and composite circuit boards. (August 2016) - Akbari, Saeed; Nourani, Amir; Spelt, Jan K.
Abstract: Printed circuit boards (PCBs) assembled with ball grid array (BGA) microelectronics packages were tested in a double cantilever beam (DCB) configuration. The results were compared for a filled and an unfilled underfill epoxy adhesive as well as a cyanoacrylate adhesive. The original fillet, formed in the underfilling process, was modified to create fillets of different sizes. Regardless of the underfill thermal and mechanical properties as well as its curing profile, the crack initiation load and the failure mode were solely a function of the size of the underfill fillet, and the failure always initiated within the PCB. Moreover, the strength of the underfilled solder joints was increased significantly (approximately 100%) by the presence of a relatively large fillet. This effect of the underfill fillet on the crack path and the fracture load was then examined in terms of differences in the stress states using a finite element model.